Platelet-vessel wall interactions in atherosclerotic disease - Langer, Harald F.; Gawaz, Meinrad (Thrombosis and Haemostasis, 2008)
During the prolonged course of atherosclerotic disease,platelets are of central importance as they contribute to the initiation of the disease, to its progression and acute exacerbation but also provide potential regenerative mechanisms. Platelets secrete chemokines and cytokines that mediate vascular inflammation and are in turn activated by substances released from cells of the vascular wall.These interactions represent positive and negative feedback loops, which in case of dysregulation may lead to development and progression of disease. Furthermore, platelet adhesion to the endothelium is critical for the initiation of atherosclerotic lesion formation in vivo. Even prior to endothelial denudation, platelet adhesion governed by disturbed flow at predilection sites for atherosclerosis induces recruitment of proathe- rosclerotic cells and release of proinflammatory mediators from all involved cell types.Finally,the pathogenetic role of platelets for late atheroclerotic events including plaque rupture, microembolism or spasms within the microcirculation is well established. However, increasing evidence indicates that platelets mediate on the other hand potential regenerative mechanisms. Platelets recruit circulating progenitor cells to sites of vascular injury. Furthermore, they influence their biological activity and maturation. Therefore,platelets contribute at all stages of vascular disease by interfering with highly dynamic processes. Understanding interactions of platelets with other circulating cells and the vascular wall is a prerequisite to understand cardiovascular disease and to identify potential therapeutic targets.
Keywords: Atherothrombosis; platelet physiology; stem cells